In vitro adsorption mechanism of acrylamide by lactic acid bacteria. (February 2019) - Shen, Yu; Zhao, Sijia; Zhao, Xiaoduo; Sun, Hongyang; Shao, Meili; Xu, Honghua
Abstract: Acrylamide (AA), a toxin that primarily exists in fried food, causes neurotoxicity, genetic toxicity, genetic mutations, and DNA damage. The present study aimed to elucidate the mechanisms by which lactic acid bacteria (LAB) adsorb AA. LAB cells were characterized via scanning electron microscopy coupled with energy dispersive X-ray spectroscopy (SEM-EDS), transcription electron microscopy (TEM), Brunauer-Emmett-Teller (BET) technique, and atomic force microscopy (AFM). Acrylamide-exposed and -unexposed bacterial cells were characterized via the zeta potential method, contact angle method, and Fourier transform infrared (FTIR) spectroscopy. Results indicated that increasing the cell wall roughness improves the AA adsorption capacity of the bacterial strains. Contact angle measurements indicated that the hydrophobic forces in the bacterial strains were associated with AA adsorption. Results of FTIR and EDS analyses indicated that the C=O, CO, and NH groups were the primary functional groups involved in the adsorption of AA by LAB, thereby demonstrating that peptidoglycan and cell wall proteins in LAB are the major components involved in AA adsorption. Taken together, our results indicated that the adsorption ability of LAB was closely associated with cell wall roughness, hydrophobicity, nitrogen-to-carbon (N/C) ratio, and functional groups. Highlights: Increasing the cell wall roughness improved the AA adsorption capacity of the bacterial strains. The surface hydrophobicity of cells was a crucial parameter in the adsorption of AA by LAB. Peptidoglycan and protein components of cell wall were involved in AA removal.